Methods In Quaternary Ecology #9. Fungi - Pirozynski, K. (Geoscience Canada, 1989)
Summary Fungi are ubiquitous in Quaternary fossiliferous deposits. Most are incidentally encountered during paleobotanical, including palynological, and paleozoological procedures and are rarely studied. Yet, explicitly paleomycological investigations reveal that fungi have considerable potential to provide data sharpening the focus of biotic and environmental reconstructions hitherto based solely on the more traditional paleontological evidence.